Inhibition of TGFβ type I receptor activity facilitates liver regeneration upon acute CCl4 intoxication in mice - Karkampouna, Sofia; Dooley, Steven (Archives of toxicology, 2016)
Liver exhibits a remarkable maintenance of functional homeostasis in the presence of a variety of damaging toxic factors. Tissue regeneration involves cell replenishment and extracellular matrix remodeling. Key regulator of homeostasis is the transforming growth factor-β (TGFβ) cytokine. To understand the role of TGFβ during liver regeneration, we used the single-dose carbon tetrachloride (CCl4) treatment in mice as a model of acute liver damage. We combined this with in vivo inhibition of the TGFβ pathway by a small molecule inhibitor, LY364947, which targets the TGFβ type I receptor kinase [activin receptor-like kinase 5 (ALK5)] in hepatocytes but not in activated stellate cells. Co-administration of LY364947 inhibitor and CCl4 toxic agent resulted in enhanced liver regeneration; cell proliferation (measured by PCNA, phosphorylated histone 3, p21) levels were increased in CCl4 + LY364947 versus CCl4-treated mice. Recovery of CCl4-metabolizing enzyme CYP2E1 expression in hepatocytes is enhanced 7 days after CCl4 intoxication in the mice that received also the TGFβ inhibitor. In summary, a small molecule inhibitor that blocks ALK5 downstream signaling and halts the cytostatic role of TGFβ pathway results in increased cell regeneration and improved liver function during acute liver damage. Thus, in vivo ALK5 modulation offers insight into the role of TGFβ, not only in matrix remodeling and fibrosis, but also in cell regeneration.